(untitled) (Scientific journal of the Fergana State University, 2023)
The given article studied the translation problems of phrasal verbs from English into Uzbek in the novel “Citadel” by A.J. Cronin. The novel “The Citadel” by A.J.Cronin was taken as a source of the article, where translation peculiarities of literary texts were studied.